2021
DOI: 10.17576/jkmjc-2021-3701-13
|View full text |Cite
|
Sign up to set email alerts
|

Exploring The Relationship of Social Media Usage and Multitasking of Social Media on Self-Efficacy and Academic Performance

Abstract: Social media usage is known to harness new lifestyle among the youth. Use of social media promotes the negative as well as positive consequences for the students in general and academic life. This study examined the relationship between social media usage, multitasking of social media, and students' academic self-efficacy on students' academic performance among Malaysian youth. The current work also evaluates the mediating effect of students' academic self-efficacy on social media usage and social media multit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…This shows that the use of social media has its advantages and has particular challenges as well. Social media usage leads to unwanted social media use (Mohammed et al, 2021). Results of research conducted by Ufuophu-Biri and Iwu (2014) concluded that high school students use social media significantly for prostitution.…”
Section: Findings and Interpretationsmentioning
confidence: 99%
“…This shows that the use of social media has its advantages and has particular challenges as well. Social media usage leads to unwanted social media use (Mohammed et al, 2021). Results of research conducted by Ufuophu-Biri and Iwu (2014) concluded that high school students use social media significantly for prostitution.…”
Section: Findings and Interpretationsmentioning
confidence: 99%
“…Academic performance is defined as an achievement of specific academic targets under the educational setting of students in a certain learning institution (Mahir, Faridah, & Norzita, 2021). Academic performance is also described as an achieved learning outcome, assessment rating, test scoring, and the GPA, which are the indicators used to measure the academic performance of a student.…”
Section: The Relationship Between Social Media Use and Academic Performance Of University Studentsmentioning
confidence: 99%
“…This scheme can help to improve the students' self-assessment and their motivation when it comes to learning and academic performance. Mahir et al (2021) have reported that the use of social media among students negatively influences their academic performance. On the one hand, according to evidence from the literature, the unnecessary heavy use of social media, especially when unmonitored, ultimately distracts students because they tend to deviate from participating in educational activities and divert their attention to non-academic activities.…”
Section: The Relationship Between Social Media Use and Academic Performance Of University Studentsmentioning
confidence: 99%
See 2 more Smart Citations